Methodological Innovations in Contemporary Qur’anic Exegesis by Muslim Intellectuals in the West: Bridging Tradition and Modernity - Siti Khodijah; Moh. Yardho; Isam Abdul Azeez T. M. (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
The study of the Qur’an in the West has developed into a robust academic discipline, marked by significant methodological transformations in interpreting the sacred text. Diverging from the classical Islamic tradition of tafsir, Western approaches frequently incorporate historical-critical methods, hermeneutics, and literary analysis. This article aims to examine the methodological evolution of Qur’anic exegesis in the West, highlighting the contributions of prominent contemporary Muslim scholars, including Fazlur Rahman’s Double Movement, Abdullah Saeed’s Contextual Approach, and Amina Wadud’s Feminist Hermeneutics. Employing a qualitative methodology rooted in library research, this study utilizes content analysis to elucidate the principles underpinning these innovative approaches. The findings indicate that these methodologies offer a more contextualized and modernly relevant reading of the Qur’an, addressing contemporary challenges while integrating historical analysis, a hierarchy of values, and principles of gender justice. These approaches facilitate the development of inclusive and adaptive interpretations that remain grounded in the fundamental values of Islam. However, they also encounter critiques, particularly concerning the application of hermeneutics to the interpretation of sacred texts. This article underscores the pivotal role of contemporary Muslim intellectuals in the West in reshaping the methodology of Qur’anic interpretation, forging a critical bridge between Islamic tradition and global academic discourse.